The Red Data Book Waterbirds in the Coastal Wetlands of the Azov-Black Sea Region of Ukraine — the Results of the August Counts 2018 and 2021 - Chernichko, J. I.; Kostiushyn, V. A.; Vinokurova , S. V. (Publishing House "Akademperiodyka" of the National Academy of Sciences of Ukraine, 2023)
The article analyses data from the August Counts of 2018 and 2021, which covered the 40 most important wetlands on the Azov-Black Sea coast of Ukraine. Of the 106 wetland bird species recorded during the censuses, 35 species are listed in the Red Data Book of Ukraine. The number of them was about 50 thousand individuals or 7.6 % of the total number of counted birds: in 2018 — 24.1 thousand individuals and in 2021 — 25.8 thousand individuals. Detailed information on the number of bird species and the list of the most important sites for each species can be found in the publication. The comparison of the current data with the previous survey period 2004‒2015 (Chernichko et al., 2018) showed that the abundance of 17 waterbird species decreased, and 7 species increased their abundance. It is assumed that these changes are caused by the aridification of the climate, leading to the drying out of the shallow parts of the region's wetlands in the second half of the summer.